ENHANCEMENT OF PHYSIO-BIOCHEMICAL PARAMETERS OF WHEAT THROUGH EXOGENOUS APPLICATION OF SALICYLIC ACID UNDER DROUGHT STRESS - S. Noreen; K. Fatima; H. U. R. Athar; S. Ahmad; K. Hussain (Journal of Animal and Plant Sciences, 2017)
Water-stress is one of the major contributing factors, which limits the productivity of most of the crops plants under arid- and semi-arid environments. The proportionate reduction is associated with crop varieties, crop growth stage, and degree of severity of water stress under the given environments. The pot culture studies were conducted to quantify the efficacy of exogenously applied salicylic acid (SA) under drought environment on wheat crop as an amerliorative measure. The treatments consisted of three factors, (a) two watering regims (no water stress, water stress at 60 %  moisture of the field capacity), (b) two levels of salicylic acid (0 mg L-1, 200 mg L-1), and (c) two wheat varieties (MH-97, S-24), arranged in a completely randomized design with four replications. The results showed that biological yield of variety MH-97 was higher by 42.71 % compared to S-24, while its quantity was reduced by 72.29 % due to drought condition. However, this reduction in biomass was mitigated by 20.1 % by spraying of 200 mg L-1 salicylic acid. MH-97 was efficient in maintaining higher chlorophyll content by 3.2 % than S-24. The SPAD values of chlorophyll were higher by 46.0 % under drought stress compared to 42.11 % under fully irrigated crop, while, it was improved by 12.5 % by spray of SA. The spray of SA caused increase in total soluble proteins by 22.8 % over untreated check. The fully irrigated crop maintained 41.1 % higher free amino acids compared to drought stressed crop, while, quantity of amino acids were enhanced by 17.28 % by spray of salicyclic acid over untreated check. MH-97 contained an amount of 10.74 mg K+ g-1 compared to S-24 having 12.0 mg K+ g-1 nutrient. The water stressed crop maintained 15.43 % higher amount of K+ compared to fully irrigated crop, and simultaneously improved by 15.34 % by spray of salicylic acid. Water stressed crop maintained 12.89 mg Na+g-1 compared to 11.26 mg g-1 under fully irrigated condition. The spray of 200 mg L-1 SA lowered the amount of  Na+ by 6.76 % compared to untreated check. The spray of SA improved 100-grain weight by 9.43 % over untreated check. MH-97 produced higher grain yield, 100-grain weight, number of spikes plant-1, number of spiklets plant-1, and number of tillers plant-1. Therefore, the spray of SA at the rate of 200 mg L-1 could rescue the wheat crop to withstand the vagaries of waterstress conditions.
Keywords: Salicylic acid; Drought stress; Wheat; Biological yield; Chlorophyll content; Free amino acids; Na+ and K+ constitutents; Grain yield and its components